A Study to Assess the Knowledge and Attitude Regarding Electroconvulsive Therapy among Caregivers of Mentally Ill Patients in Selected Government Medical College Attached Hospital and Hospital for Mental Health of Madhya Pradesh State with a View to Devel - Kumar Meena, Suraj; Samuel, Jim (International Journal of Nursing and Medical Investigation, 2024)
Background: Mental disorders are broadly classified as neurosis and psychosis. Neurosis includes anxiety neurosis, depressive neurosis, hysterical neurosis, phobic neurosis, etc., psychosis mainly includes schizophrenia, depression, mania, and some special disorders such as childhood disorder, personality disorder, substance abuse, and mental retardation. Methods: This study is aimed to assess the knowledge and attitude regarding ECT among caregivers of mentally ill patients in selected government medical college attached hospital and hospital for mental health of Madhya Pradesh state with a view to develop pamphlet on it, the survey type of approach is considered the most appropriate. Results: In relation to the finding of the study, it was revealed that the majority of respondents 25% had poor knowledge, 67% had an average knowledge and few 8% had good knowledge regarding ECT among caregivers of mentally ill patients. Related to finding of attitude this study revealed that 62 (62%) samples had negative attitude and 38 (38%) samples had positive attitude. Conclusion: Nurse can increase awareness regarding ECT among the caregivers of the mentally ill. Nurse should enhance IEC activities to remove the misconceptions regarding Stigma and Discrimination in regard to mental illness. This will help nursing profession to make the caregivers more aware of promotion and protection of health during mental illness and receiving ECT.